EMOTIONAL INTELLIGENCE OF MADRASAH PRINCIPALS IN BUILDING EFFECTIVE LEADERSHIP BEHAVIOR - Fauzi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Emotional intelligence is an important part in building effective leadership behavior, and is believed to be able to color the dynamics of leadership so far, so that it can then increase the loyalty of individual performance in the organization. Therefore, a leader must be able to move, arouse, motivate and inspire other individuals in the organization. Leadership behavior in Islamic educational institutions is an actualization of the internalization of values inherent in his personality and emotional intelligence. Thus the results of the discussion of emotional intelligence-based leadership can give birth to two aspects, including: a) emotional intelligence-based leadership is more effective and has an influence on the loyalty of individual performance in Islamic education organizations, where high and low emotional intelligence also affects the high and low loyalty of individual performance. b) the emotional intelligence of a leader cannot be measured by the level of education, and has good emotional intelligence.